Internal Auditory Canal Dural Enhancement in Granulomatosis with Polyangeitis Disease - Juan Carlos Izquierdo Velásquez; Luis Felipe Romero Moreno (Case Reports in Neurological Medicine)
Diffuse dural enhancement of the internal auditory canal in T1-weighted gadolinium-enhanced magnetic resonance imaging could be a helpful and early clinical sign in a very aggressive limited granulomatosis with polyangeitis disease, called previously Wegener Disease (WD).